2021
DOI: 10.1083/jcb.202105092
|View full text |Cite
|
Sign up to set email alerts
|

LUBAC regulates ciliogenesis by promoting CP110 removal from the mother centriole

Abstract: Primary cilia transduce diverse signals in embryonic development and adult tissues. Defective ciliogenesis results in a series of human disorders collectively known as ciliopathies. The CP110–CEP97 complex removal from the mother centriole is an early critical step for ciliogenesis, but the underlying mechanism for this step remains largely obscure. Here, we reveal that the linear ubiquitin chain assembly complex (LUBAC) plays an essential role in ciliogenesis by targeting the CP110–CEP97 complex. LUBAC specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…How does PRP-8 act from the ciliary base to promote cilium formation and regeneration? Recent studies reported that PRPF8 functions as the receptor of linear ubiquitin chains at the ciliary base to facilitate CP110-CEP97 complex removal at the initial stage of ciliogenesis , Shen, Yuan et al 2022. Such a role of PRPF8 may apply to cilium regeneration from the existing middle ciliary segment, which suggests that PRPF8 must play additional roles from the ciliary base.…”
Section: Discussionmentioning
confidence: 99%
“…How does PRP-8 act from the ciliary base to promote cilium formation and regeneration? Recent studies reported that PRPF8 functions as the receptor of linear ubiquitin chains at the ciliary base to facilitate CP110-CEP97 complex removal at the initial stage of ciliogenesis , Shen, Yuan et al 2022. Such a role of PRPF8 may apply to cilium regeneration from the existing middle ciliary segment, which suggests that PRPF8 must play additional roles from the ciliary base.…”
Section: Discussionmentioning
confidence: 99%
“…CP110 is prone to a remarkably complex regulatory network that involves four ubiquitin E3 ligases (SCF CyclinF , EDD1-DYRK2-DDB1-VPRBP, LUBAC and NEURL4), two DUBs (USP33 and OTULIN) and two kinases (TTBK2 and MARK4). [32][33][34][35][36][37] In cycling cells, CP110 becomes ubiquitylated for proteasomal degradation by SCF CyclinF , another Cullin-RING ligase that utilises CyclinF as a substrate receptor. [32] This process is restricted to the G 2 /M-phase of the cell cycle, which is at least partially due to the counteracting activity of the DUB USP33 that deubiquitylates and thereby protects CP110 during S and early G 2 .…”
Section: The Cep97-cp110 Capping Complexmentioning
confidence: 99%
“…CP110 is prone to a remarkably complex regulatory network that involves four ubiquitin E3 ligases (SCF CyclinF , EDD1‐DYRK2‐DDB1‐VPRBP, LUBAC and NEURL4), two DUBs (USP33 and OTULIN) and two kinases (TTBK2 and MARK4). [ 32–37 ]…”
Section: Targeting Negative Regulators To Initiate Ciliogenesismentioning
confidence: 99%
See 2 more Smart Citations